Study of the Key Mechanical Properties of Welded Hollow Spherical Joints after Uniform Corrosion - Qiu, Feng; Wang, Yinsong; Gao, Yu; Zhang, Zhiwei; Qian, Hongliang; Wang, Huajie; Fan, Feng (Periodica Polytechnica Civil Engineering, 2023)
The welded hollow spherical joint is the most common form of the spatial grid structure, but the corrosion treatment at the joint is difficult. There are many corrosion problems of the welded hollow spherical joint in the actual structure, which brings hidden problems to structural safety. To study the effects of uniform corrosion on the key mechanical properties of welded hollow spherical joints, the joint refinement FEM in one typical size is built considering the effect of uniform corrosion through the method of the element birth and death, and the tensile, compressive, and bending performance of the FEM has been analyzed. Based on the analysis results, the relation curves between the three bearing capacities of the welded hollow spherical joint and the uniform corrosion degree are given. The results show that the influence of early corrosion on the joint tensile and compressive performance is not obvious. After corrosion to a certain extent, the loss of tensile and compressive capacity has a significant linear relationship with the degree of corrosion, and the loss of bending capacity has a significant quadratic curve relationship with the degree of corrosion from the initial stage. This study can provide a theoretical reference for a better understanding of the mechanical properties of welded hollow spherical joints in one typical size after corrosion to evaluate structural safety.